Influence of Student’s Non-Cognitive and Cognitive Trait on their Proposed Entrepreneurial Ventures’ Initial Set Up Decision - Aaijaz, Naila; PhD; Dahlan Bin Ibrahim, Mohamed; PhD (British Journal of Marketing Studies, 2013)
The current study is intended to study the influence of non-cognitive characteristics and cognitive trait i.e. learned by experience, demographic factors, entrepreneurial education and others on their proposed entrepreneurial initial set up decision.Research inference is derived from the samples of 150 entrepreneurial program students during the period 2011-2012 selected from University Malaysia Kelantan (UMK), University Putra Malaysia (UPM) and University Utara Malaysia (UUM). Previous studies have endeavored to measure the effects of one or more variables on entrepreneurial ventures’ initial set up decision, but while the main implication of this study is to collect all related variables in an integrated model and to investigate cumulative effects of these variables on the entrepreneurial key decision taking ability of entrepreneurs. The present study findings are based on the cumulative effects of entrepreneur’s non-cognitive attributes and cognitive notions and traits on the ability of entrepreneurial key decision taking ability which have not been investigated in previous studies yet.